“No one listened to me for ten years” : the experience of people with fibromyalgia in seeking a diagnosis & receiving appropriate help within primary health care in Iceland : a qualitative study - Björg Hákonardóttir 1992- (2024)
Aim: Fibromyalgia is a chronic primary pain condition that causes various symptoms such as pain, fatigue, affective- and cognitive problems. Studies indicate that doctors can be prejudiced towards fibromyalgia and that patients are often dissatisfied with the care they receive. The current study used thematic framework analysis to investigate fibromyalgia patients' experiences of seeking care and diagnosis within the primary health care (PHC) system in the metropolitan area of Iceland. Design: Thematic framework analysis. Method: The sample included 5 female participants, ages 20-38, suffering from fibromyalgia. The participants were interviewed through a semi-structured interview designed for the current study. The interview was split into three sections: one focusing on the time before diagnosis, one on the diagnostic process and one on treatment/support after FM was diagnosed. Interviews were recorded, transcribed and analysed for themes. Results: The analysis revealed three core themes and eight subthemes. The core themes were: (1) FM‘s impact on daily life which concerns the effect the disease has on participants lives; (2) Seeking care which concerns participants‘ experiences within the PHC system; and (3) Resources which concerns treatment for fibromyalgia and attitudes towards treatment. Conclusion: Findings suggest that FM patients are not receiving the care they need in the PHC system. Additionally doctor’s knowledge of FM and available resources is lacking. Key words: Fibromyalgia, FM, chronic pain, primary health care, PHC, doctors.